Forged in flames: indigeneity, forest fire and geographies of blame in the Philippines. Issue 4 (1st October 2020) - Smith, Will; Dressler, Wolfram H.
ABSTRACT: The forests of Southeast Asia are represented as increasingly 'at-risk' to fire, constituting a regional fire politics concerned with the management and organisation of environmental blame. State governments often place culpability for this increasing flammability on histories of deforestation that disproportionately blame Indigenous peoples who now face a correspondingly large burden in conservation schemes. By tracing the history of fire management from the colonial period to the 1980s, this paper explores how the management of forests and fire in the Philippines has been shaped over time with imperatives to govern and economically exploit upland spaces. While these histories clearly point to a political economy of knowledge production, they also show how forest governance in the Philippines has worked to construct ethnic difference through policies and practices that naturalise livelihoods, spaces and qualities to essentialised 'tribal' uplanders. To understand the contemporary geography of blame that surrounds forest fires and deforestation in the Philippines and Southeast Asia more broadly, we argue for a more nuanced examination of 'the uplands' as a post-colonial geography co-constituted with the historical production of indigeneity and environmental knowledge. We conclude by emphasising the historical role of colonial forest and land management institutions in fashioning lasting socio-spatial differences.